Online election system with fingerprint verification - Voon, Buang Hong. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Every year, each local university in Malaysia will have the election to give their student a choice to decide the student's representative. In University Malaysia Sarawak (UNIMAS), the student's representative will become a member of Student Representative Council (Majlis Perwakilan Pe/ajar, MPP). They are the middle person between the university administrators and the students. The developed system; Online Election System with Fingerprint Verification provides a high security election system for the university. This system provides the service of calculating and giving the final result of the election accurately. Besides tha~ the system also provides the service of automatic student verification and attendance taking during voting day with fingerprint technology.